2014
DOI: 10.1016/j.accfor.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure on climate change: Analysing the UK ETS effects

Abstract: HIGHLIGHTS• Study organisations that took part in the UK Emissions Trading Scheme (UK ETS).• Compare disclosure produced on climate change in annual and standalone reports.• Suggest a coding instrument based on a synthesis of disclosure recommendations.• UK ETS did influence corporate environmental disclosure on climate change.• Disclosures in annual and standalone reports are different and may be complementary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The selection of standalone sustainability reports is consistent with numerous disclosure studies in the area of social and environmental accounting which have either investigated both annual reports and stand-alone reports or only stand-alone reports (deAguiar & Bebbington 2014;Hooks & van Staden 2011). Moreover, as the sustainability report is a stand-alone report on corporate social and environmental performance issues, it may be inferred that the best understanding on a company's views on these issues can be gained from this report.…”
Section: Research Methods Research Approachmentioning
confidence: 55%
See 1 more Smart Citation
“…The selection of standalone sustainability reports is consistent with numerous disclosure studies in the area of social and environmental accounting which have either investigated both annual reports and stand-alone reports or only stand-alone reports (deAguiar & Bebbington 2014;Hooks & van Staden 2011). Moreover, as the sustainability report is a stand-alone report on corporate social and environmental performance issues, it may be inferred that the best understanding on a company's views on these issues can be gained from this report.…”
Section: Research Methods Research Approachmentioning
confidence: 55%
“…While increasing number of studies on corporate social and environmental disclosure in the past decade have continued to investigate new and unexplored aspects of environmental reporting including climate change (or carbon) reporting (deAguiar & Bebbington 2014;Hrasky 2012;Solomon et al 2011), greenhouse gas emissions reporting (Bebbington & Larinaga-Gonzalez 2008;Milne & Grubnic 2011;Rankin, Windsor & Wahyuni 2011) and water reporting (Morikawa, Morrison & Gleick 2007;Rahaman, Lawrence & Roper 2004); social reporting has continued to be largely neglected and to remain in the shadows of environmental reporting studies. This is despite continuing criticism by leading scholars on this imbalance of focus amongst social and environmental accounting researchers (Deegan 2002;Mathews 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Change in accounting frameworks to measure and disclose carbon information and costs is seen as necessary especially under carbon pricing mechanisms (Boston and Lempp, 2011;Milne and Grubnic, 2011;Martinov-Bennie, 2012). Many studies have looked at the nature of carbon disclosure itself (Andrew and Cortese, 2011;Rankin et al, 2011;de Aguiar and Bebbington, 2014;Haslam et al, 2014;Halkos and Skouloudis, 2016) and the association between disclosure and carbon and economic performance (Griffin et al, 2012;Chapple et al, 2013;Matsumura et al, 2013;Luo and Tang, 2014). Carbon management accounting is argued to be valuable in various decision settings, such as evaluating product emissions and costs, identifying emission reduction and investment possibilities and facilitating decisions across different organisational functions Stechemesser and Guenther, 2012;Tsai et al, 2012).…”
Section: Carbon Performance Management and Carbon Management Systemmentioning
confidence: 99%
“…Most previous studies of GHG emission disclosure have been conducted in developed and Western countries, such as Australia (see Andrew & Cortese, ; Choi et al, ; Hrasky, ; Li, Eddie, & Liu, ; Rankin, Windsor, & Wahyuni, ; Wang, Li, & Gao, ), the United Kingdom (Baboukardos, ; Chithambo & Tauringana, ; de Aguiar & Bebbington, ), the United States (see Kim & Lyon, ; Lewis, Walls, & Dowell, ; Stanny, ; Stanny & Ely, ), and Canada (see Ben‐Amar & McIlkenny, ). Choi et al () analysed the reactions of Australia's largest 100 companies during the period 2006–2008 when the Australian government announced a series of regulations regarding GHG emission disclosure; they found that the level of disclosure was 46.0%.…”
Section: Introductionmentioning
confidence: 99%